1997
DOI: 10.1086/133956
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Magnitudes of the RR Lyrae Stars

Abstract: ABSTRACT. We present a new calibration of the relationship between the absolute magnitudes and metal abundances, [Fe/H], of RR Lyrae stars. Temperatures inferred from optical and near-infrared color indices and the new Kurucz models are utilized in conjunction with Baade-Wesselink solutions to derive absolute magnitudes. Temperatures inferred from the optical and near-infrared photometry are -200-300 K higher for the variables than those given from (V-K) color indices and the older Kurucz models. We find M v =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 18 publications
4
28
1
Order By: Relevance
“…The dependence of this luminosity on metallicity ranged from a slope ΔM V (RR)/Δ[Fe/H] ∼ 0.27−0.37 mag dex −1 (Sandage 1993;McNamara 1997;Feast 1997;Reid 1997) to 0.13−0.23 mag dex −1 (Fernley et al 1998, and references therein; Chaboyer 1999; Gratton et al 2004;R05). A fairly accurate and widely quoted result is the slope of 0.214 ± 0.047 from the photometric and spectroscopic study of about 100 RR Lyrae stars in the bar of the LMC by Clementini et al (2003), who found that a unique linear relation over the entire considered metallicity range was adequate to fit the data.…”
Section: The Assumed Metallicitymentioning
confidence: 99%
“…The dependence of this luminosity on metallicity ranged from a slope ΔM V (RR)/Δ[Fe/H] ∼ 0.27−0.37 mag dex −1 (Sandage 1993;McNamara 1997;Feast 1997;Reid 1997) to 0.13−0.23 mag dex −1 (Fernley et al 1998, and references therein; Chaboyer 1999; Gratton et al 2004;R05). A fairly accurate and widely quoted result is the slope of 0.214 ± 0.047 from the photometric and spectroscopic study of about 100 RR Lyrae stars in the bar of the LMC by Clementini et al (2003), who found that a unique linear relation over the entire considered metallicity range was adequate to fit the data.…”
Section: The Assumed Metallicitymentioning
confidence: 99%
“…The identified radial modes are listed in the last column of Table 3. McNamara (2000McNamara ( , 2001 suggested that the light amplitude and the degree of asymmetry of the light curves are useful parameters for identifying the pulsating modes. Generally, this method is very useful for systems with a small number of pulsators and /or no double-radial mode stars.…”
Section: Radial Mode Identificationmentioning
confidence: 99%
“…The P-L relation of SX Phoenicis stars in globular clusters is very useful to obtain the distance moduli of the clusters and nearby galaxies ( McNamara 1995). However, it is not easy to define well the P-L relation from observations because there is often a mixture of different pulsation modes (Jeon et al 2003;McNamara 2001).…”
Section: Period-luminosity Relationmentioning
confidence: 99%
“…On the other hand, astronomers utilizing a variety of other techniques (e.g., Sandage 1993 ;McNamara 1997aMcNamara , 1997bFeast 1997 ;Reid 1997) have found a steeper slope, and somewhat brighter zero point D0.95 mag. An Z0.30 accurate knowledge of the absolute magnitudes of the RR Lyrae stars is important since they are used to establish the luminosity of the horizontal branches of globular clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Fusi Pecci et al (1996) have obtained color-magnitude diagrams (CMDs) of eight globular clusters in M31 down to D1 mag fainter than their horizontal branches (HB) with the Hubble Space T elescope. The cluster metallicities determined with the aid of the position of observed giant branches in the plane range from [0.20 (McNamara 1997a(McNamara , 1997bSandage 1993). The Sandage study in particular was based on stars in the entire metallicity range from metal-poor to metal-strong variables.…”
mentioning
confidence: 99%